2013
DOI: 10.3109/10428194.2012.752081
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum high mobility group box 1 in hematological malignancies complicated with systemic inflammatory response syndrome and effect of recombinant thrombomodulin

Abstract: High mobility group box 1 (HMGB1) mediates inflammation. We investigated the role of serum HMGB1 in 54 patients with hematological malignancies with and without systemic inflammatory response syndrome (SIRS). There was no difference between groups 1 (complete remission of hematological disease: n = 13) and 2 (no remission: n = 16) in serum HMGB1 levels. However, those of group 3 (complicated by SIRS: n = 25) were significantly higher (vs. group 1: p < 0.001 and vs. group 2: p = 0.008, respectively). Seventeen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In addition, inflammatory function of HMGB1 has been further discovered that HMGB1 may be capable of prolonging and sustaining inflammatory processes by inducing macrophages to release cytokines and inflammatory mediators such as TNF- α , IL-1 α , IL-1 β , and IL-8 when released into an extracellular environment [ 19 ]. In particular, numerous studies have emphasized the important role of proinflammatory cytokines in the mechanism that severe acute pancreatitis develops systemic inflammatory response syndrome, multiple organ failure, and even death [ 7 , 20 ]. For instance, increased HMGB1 levels were found in the plasma of patients with chronic lymphocytic leukemia when compared to healthy controls, and the concentration of HMGB1 is suggested to be correlated with the absolute count of lymphocyte [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, inflammatory function of HMGB1 has been further discovered that HMGB1 may be capable of prolonging and sustaining inflammatory processes by inducing macrophages to release cytokines and inflammatory mediators such as TNF- α , IL-1 α , IL-1 β , and IL-8 when released into an extracellular environment [ 19 ]. In particular, numerous studies have emphasized the important role of proinflammatory cytokines in the mechanism that severe acute pancreatitis develops systemic inflammatory response syndrome, multiple organ failure, and even death [ 7 , 20 ]. For instance, increased HMGB1 levels were found in the plasma of patients with chronic lymphocytic leukemia when compared to healthy controls, and the concentration of HMGB1 is suggested to be correlated with the absolute count of lymphocyte [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, patients with hematologic malignancies were just a small part and not analyzed alone in their study. In the study by Inoue Y and his group, the plasma levels of HMGB1 were five times higher in leukemic patients with SIRS than those without, and more than half of the former part developed DIC [40]. Therefore, we predicted that HMGB1 may play a role in DIC with leukemia.…”
Section: Discussionmentioning
confidence: 90%
“…High serum HMGB1 levels are observed in acute respiratory distress syndrome and multiorgan distress syndrome, and elevated levels are correlated with the severity of sepsis, burns, and pancreatitis [16][17][18]. We previously reported that serum HMGB1 levels were significantly higher in patients with hematological malignancy with SIRS, caused by complications like tumor lysis syndrome or DIC, than in patients with hematological malignant disease without SIRS [19]. Outcomes in rhTM-treated patients with aGVHD, veno-occlusive disease, or intestinal transplant-associated microangiopathy that have developed after allo-HSCT have been reported to be successful [20][21][22].…”
Section: Discussionmentioning
confidence: 99%